1‐naphthylacetic‐acid‐functionalized polyacrylate‐coated urea with dual controlled‐release properties. Issue 2 (3rd November 2012) - Qiu, Xiaoyun; Zhu, Dacai; Tao, Shuming; Chen, Chao; Ren, Xueqin; Hu, Shuwen
Abstract Esters derived from 1‐naphthylacetic acid (NAA) and polyacrylate were synthesized and a dual controlled‐release formulation was developed by coating fertilizers with these esters. FT‐IR, 1H NMR, TGA, and DSC were used to characterize the synthesized polymers, and the mechanical properties were also tested. Urea granules were coated with NAA esters, and the release rates of urea from the coated granules in water were measured. NAA release from the esters was performed in different buffer solutions and in soil. The results showed that the coated fertilizers were able to release urea in a controlled pattern and that NAA could be slowly released from membranes of the esters in both buffer solutions and in soil through hydrolysis. The coated fertilizer's availability could last more than 28 days and that of NAA could last more than 12 months, which suggested that the prepared CRF possessed dual controlled‐release of urea and NAA. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013